2019
DOI: 10.3389/fpsyg.2019.00862
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation on the Elicitation of Subjective Distributions

Abstract: Elicitation methods aim to build participants' distributions about a parameter of interest. In most elicitation studies this parameter is rarely known in advance and hinders an objective comparison between elicitation methods. In two experiments, participants were first presented with a fixed random sequence of images and numbers and subsequently their subjective distributions of percentages of one of those numbers was elicited. Importantly, the true percentage was set in advance. The first experiment tested w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…While NLP enables parsing large amounts of text and semantic differential rating scales enable to capture quantitative data, EKE is a technique to extract knowledge from human experts in relation to a topic of interest [ 4 , 65 , 78 ]. Some of the classic EKE techniques are interviews, protocol analysis, concept sorting, among others [ 78 ].…”
Section: Ai Meets Nb: Towards Ai-powered Nbmentioning
confidence: 99%
See 1 more Smart Citation
“…While NLP enables parsing large amounts of text and semantic differential rating scales enable to capture quantitative data, EKE is a technique to extract knowledge from human experts in relation to a topic of interest [ 4 , 65 , 78 ]. Some of the classic EKE techniques are interviews, protocol analysis, concept sorting, among others [ 78 ].…”
Section: Ai Meets Nb: Towards Ai-powered Nbmentioning
confidence: 99%
“…Some of the classic EKE techniques are interviews, protocol analysis, concept sorting, among others [ 78 ]. Other approaches based on statistics, probability, and decision-making theories, elicit quantitative knowledge by obtaining information about an uncertain quantity from a person’s subjective experience and converting it into a probability distribution [ 4 , 33 , 65 ]. Each EKE approach can be used for categorical (e.g., interviews) or numeric topics (e.g., via subjective probability distributions) but the key feature of EKE is that it allows eliciting judgments from people in a highly systematic and scientific fashion.…”
Section: Ai Meets Nb: Towards Ai-powered Nbmentioning
confidence: 99%
“…The results of the experiment showed that the group with instructions estimated the parameter more accurately than the group without. 11 The author investigates the effect of knowledge on subjective probability estimation in this study. Based on literature review, the second hypothesis is formulated: Hypothesis 2 (H2): The level of knowledge provided to the participants affects subjective probability estimation.…”
Section: Knowledgementioning
confidence: 99%
“…An elicitation process involves extracting information about parameters of interest (θ) from the subjective experience of a person (expert) and expressing it as a probability distribution (prior distribution) Barrera-Causil et al, (2019) [2]. Thus, for expert i, a real function x i (θ) (prior distribution) is elicited, and for a grid of m equally spaced points…”
Section: Definitions 21 Elicitation Of Probability Distributionsmentioning
confidence: 99%
“…Hence, we believe that the probability distributions of each expert can be classified and their opinions represented using clusters of beliefs. Thus, Bayesian inference can be carried out in parallel by considering each cluster of priors and a decision can be arrived at via experts' criteria (Barrera-Causil et al, 2019) [2]. On the other hand, classifying probability distributions is an essential task in different areas.…”
Section: Introductionmentioning
confidence: 99%